2022
DOI: 10.3390/brainsci12091195
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Parameter-Guided Anesthesia for Prevention of Emergence Delirium in Children

Abstract: Background: Emergence delirium (ED) usually occurs in children after surgery with an incidence of 10−80%. Though ED is mostly self-limited, its potential injuries cannot be ignored. Whether electroencephalography (EEG)-parameter-guided anesthesia could reduce the incidence of ED in pediatric surgery has not been fully discussed to date. Methods: Fifty-four boys aged 2–12 years undergoing elective hypospadias surgery under sevoflurane anesthesia were selected. In the EEG-parameter-guided group (E group), sevofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…EEG guidance also enabled greater appreciation of the higher anesthetic requirements in younger children aged 1–2 years compared to children aged > 2 years. Han et al [ 72 ] studied 54 children aged 2–12 years undergoing urological surgery and demonstrated that EEG-guided anesthesia management reduced the intraoperative sevoflurane dose and incidence of emergence delirium (ED). Weber et al [ 73 ] reported that in children aged 12–17 years underdoing deep sedation for gastrointestinal endoscopy, propofol dosing guided by the Narcotrend index led to faster recovery, lower propofol consumption, and fewer episodes of oversedation than propofol dosing according to clinical surrogate parameters of depth of hypnosis.…”
Section: Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…EEG guidance also enabled greater appreciation of the higher anesthetic requirements in younger children aged 1–2 years compared to children aged > 2 years. Han et al [ 72 ] studied 54 children aged 2–12 years undergoing urological surgery and demonstrated that EEG-guided anesthesia management reduced the intraoperative sevoflurane dose and incidence of emergence delirium (ED). Weber et al [ 73 ] reported that in children aged 12–17 years underdoing deep sedation for gastrointestinal endoscopy, propofol dosing guided by the Narcotrend index led to faster recovery, lower propofol consumption, and fewer episodes of oversedation than propofol dosing according to clinical surrogate parameters of depth of hypnosis.…”
Section: Search Strategymentioning
confidence: 99%
“…Three studies examined the association between EEG-guided anesthesia and the development of ED [ 72 , 80 , 81 ]. The first study compared the incidence of ED in children targeting anesthesia to an EEG SEF95 of 10–15 Hz vs. no EEG guidance [ 72 ].…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Regional cerebral oxygenation can be monitored through Near Infrared Spectroscopy (NIRS), a technology that gives instant information needed for safeguarding brain function during surgery [ 66 ]. Also, cerebral activity during anesthesia and surgery is commonly evaluated with sedation monitors (BIS or Sedline, to cite some), which can show the presence of different waves instant by instant, allowing the titration of drugs to achieve the desired effects and reduce adverse events (delirium, for instance) [ 67 ] ( Figure 2 ).…”
Section: Pediatric Anesthesia During Masmentioning
confidence: 99%
“…Postoperative delirium (POD) is a self-limiting condition that occurs within hours to days after surgery. 1 , 2 It is marked by manifestations of brain dysfunction including acute disturbances in attention, cognitive function, and thought process. 3 POD occurs in 10–50% of patients after general surgery and is associated with a prolonged hospital stay, long-term cognitive impairment, poor quality of life, and increased mortality.…”
Section: Introductionmentioning
confidence: 99%